Analyzing Nicotinamide Adenine Dinucleotide Phosphate Oxidase Activation in Aging and Vascular Amyloid Pathology - Radbruch, Helena; Mothes, Ronja; Bremer, Daniel; Seifert, Stefanie; Köhler, Ralf; Pohlan, Julian; Ostendorf, Lennard; Günther, Robert; Leben, Ruth; Stenzel, Werner; Niesner, Raluca Aura; Hauser, Anja E. (Frontiers in Immunology, 2017)
In aging individuals, both protective as well as regulatory immune functions are declining, resulting in an increased susceptibility to infections as well as to autoimmunity. NADPH oxidase 2-deficiency in immune cell subsets has been shown to be associated with aging. Using intravital marker-free NAD(P)H fluorescence lifetime imaging, we have previously identified microglia/myeloid cells and astrocytes as main cellular sources of NADPH oxidases (NOX) activity in the CNS during neuroinflammation, due to an over-activation of NOX). The over-activated NOX enzymes catalyze the massive production of the highly reactive O2–, which initiates in a chain reaction the overproduction of diverse reactive oxygen species (ROS). Age-dependent oxidative distress levels in the brain and their cellular sources are not known. Furthermore, it is unclear whether in age-dependent diseases oxidative distress is initiated by overproduction of ROS or by a decrease in antioxidant capacity, subsequently leading to neurodegeneration in the CNS. Here, we compare the activation level of NOX enzymes in the cerebral cortex of young and aged mice as well as in a model of vascular amyloid pathology. Despite the fact that a striking change in the morphology of microglia can be detected between young and aged individuals, we find comparable low-level NOX activation both in young and old mice. In contrast, aged mice with the human APPE693Q mutation, a model for cerebral amyloid angiopathy, displayed increased focal NOX over-activation in the brain cortex, especially in tissue areas around the vessels. Despite activated morphology in microglia, NOX over-activation was detected only in a small fraction of these cells, in contrast to other pathologies with overt inflammation as experimental autoimmune encephalomyelitis (EAE) or glioblastoma. Similar to these pathologies, the astrocytes majorly contribute to the NOX over-activation in the brain cortex during cerebral amyloid angiopathy. Together, these findings emphasize the role of other cellular sources of activated NOX than phagocytes not only during EAE, but also in models of amyloid pathology. Moreover, they may strengthen the hypothesis that microglia/monocytes show a diminished potential for clearance of amyloid beta protein.